Antimicrobial activity of polyethyleneimine/polyurethane (PEI/PU) colloidal films - Liu, Minghui (University of Waterloo, 2021)
With the occurrence of healthcare associated infections (HAIs), the development of novel antimicrobial materials has drawn significant research attention. However, developing an antimicrobial material that can be long-term effective and environmentally friendly without cytotoxicity is still a technical challenge and normally results in large production costs. In this thesis research, we fabricated, characterized and evaluated a polyethyleneimine/polyurethane (PEI/PU) colloidal film for antimicrobial coating applications. Following the previous work in our group, the colloidal film was obtained by introducing polyethyleneimine into a waterborne polyurethane. This colloidal film was found having excellent mechanical properties. From tensile tests it was found that the PU/PEI composites displayed superior mechanical properties compared to pure PU with an ultimate tensile strength of 23 MPa compared to 18 MPa for pure PU. In addition to tensile tests, scratch tests were performed on the coatings. It was found that at 5 wt% PEI the coatings displayed the best abrasion resistance at 2000 g of applied force on the tip compared to 1200 g for pure PU. The antimicrobial activities were investigated in this work with the hypothesis of PU/PEI colloidal films being a dual-functional antibacterial material. The ion-releasing activity and contact-killing efficiency of PU/PEI colloidal films were tested separately. Though there have not been conclusive results showing the existence of ion-releasing antibacterial working principle, a high killing rate of contact-active antibacterial activity was observed. Furthermore, explorative evaluations were performed to check possible virucidal effect against baculovirus.
Keywords: waterborne polyurethane; antimicrobial polymer; polyethyleneimine; colloidal film; cationic antibacterial polymer